Asymmetric Synthesis of Chiral 1,3-Dimethyl Units Through a Double Michael Reaction of Nitromethane and Crotonaldehyde Catalyzed by Diphenylprolinol Silyl Ether - Hayashi, Yujiro; Toda, Shunsuke (Synlett, 2019)
An efficient synthetic route to install chiral 1,3-dimethyl units through a double Michael reaction of crotonaldehyde and nitromethane catalyzed by diphenylprolinol silyl ether is developed. Either 1,3-syn- or 1,3-anti-dimethyl units are obtained selectively depending on the enantiomer of the diphenylprolinol silyl ether catalyst used. The side chain of pneumocandin B0 is synthesized enantioselectively by using the present method as a key step.
Keywords: organocatalyst; Michael reaction; asymmetric synthesis; diastereoselective reaction; diphenylprolinol silyl ether